Aplicação do princípio jurídico da precaução no processo administrativo de liberação dos cultivares e dos transgênicos LL62 e GM Embrapa 5.1 - SOUSA, Narliane Alves de Souza e (2012)
The current panorama experienced by society, from the perspective of genetic improvement, especially the vegetables, attracts the questioning about application of legal principle of precaution, this due to scientific uncertainty of possible damage that they may trigger on long term. Thus, due to changes in environmental conditions and effect of necessary human health by use of biotechnology has brought the principal object of this work is to analyze the precautionary principle and the process of releasing plants genetically altered and improved, in particular of cultivars and of transgenic crops under the legal perspective. Because two processes were analyzed for release of genetically modified organisms, which are the "rice LL62" Bayer and the bean "GM Embrapa 5.1" of Embrapa, being that the first is an application of experiment and the second a request for marketing. Noting that both the studies of genetic improvement and the protection of the environment are guarded by the Federal Constitution of 1988. Also, due the questions in the legal field study examined whether the Commission's release process Tecnic National de Biossegurança CTNBio follows the fulfilment of the minimum specifications required by the precautionary principle and whether they are sufficient to ensure food safety and to avoid possible irreversible degradation of the environment. Social and legal context, remaining evidenced differences polemics in relation to the said applications for the release and the precautionary principle, which encounters a single technological challenge to be respected. Thus, the Judiciary, under the Constitutional vision, the environment and administrative nature, should grant the scientific advancement with the fulfilment of minimum requirements for these releases or require the fulfilment of bureaucracy hailed by society?